Industrial experience in the implementation of clinker-free binders of alkaline activation - M. Sh. Salamanova; Z. Kh. Ismailova (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. Issues related to the search for new, less energy- and material- intensive binders have long been on the agenda of many world environmental forums, since the carbonate technology of Portland cement entails pollution of the surrounding atmosphere and habitat, and the price of this product is unjustifiably growing. In our opinion, alkaline cements could contribute to the construction industry. Within the framework of this work, research results have been obtained that confirm the effectiveness of the development of a clinker-free technology for producing alkaline-mixed binders and composites based on them using aluminosilicate additives, both natural and technogenic origin.Method. The methods of electron microscopy and differential thermal analysis make it possible to study the nature of the components and the processes of formation of the structure of the cement stone. Waste from the cement industry has the appropriate granulometric and chemical composition, the aluminosilicate mineralogy of the studied powders confirms their compliance with the ready-made raw mix of Portland cement clinker, which is the key to the possibility of their effective use.Result. The carried out differential thermal analyzes confirmed the presence of the following phases in the composition of cement stone on binding bonds "cement dust - alkaline activator" of zeolite, calcite, mica type muscovite, montrillonite, magnesium oxide, calcium sulfoaluminates, ettringite structure, calcium hydrochloraluminate, calcium hydrosilicate, calcium hydrosilicate calcium.Conclusion. The obtained regularities of the processes of formation of the structure of the cement binder "waste of the cement industry - Na2SiO3", will transform these developments to create strong and durable artificial building composites competing with concretes on Portland cement.